2006
DOI: 10.3386/w12304
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Poor Health on Education: New Evidence Using Genetic Markers

Abstract: This paper examines the influence of health conditions on academic performance during adolescence. To account for the endogeneity of health outcomes and their interactions with risky behaviors we exploit natural variation within a set of genetic markers across individuals. We present strong evidence that these genetic markers serve as valid instruments with good statistical properties for ADHD, depression and obesity. They help to reveal a new dynamism from poor health to lower academic achievement with substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 74 publications
2
56
0
Order By: Relevance
“…Another potential contribution to social science, already being actively pursued (e.g., 5,6), is the use of genetic markers as instrumental variables in (nongenetic) empirical work. In order for the gene-as-instrument to be valid, not only must the marker be robustly associated with the "endogenous regressor," but all of the behaviors associated with that marker must be understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential contribution to social science, already being actively pursued (e.g., 5,6), is the use of genetic markers as instrumental variables in (nongenetic) empirical work. In order for the gene-as-instrument to be valid, not only must the marker be robustly associated with the "endogenous regressor," but all of the behaviors associated with that marker must be understood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if specific genetic markers can be identified that are associated with a behavioral trait, then such predictive markers may shed light on the biological pathways underlying that trait (3,4). If a set of genetic markers is sufficiently predictive, then these markers could be used in social science research as control variables, as instrumental variables (5,6; for critical perspectives, see refs. 7,8) or, under certain conditions, as factors for identifying at-risk individuals (1)(2)(3).…”
mentioning
confidence: 99%
“…The three economic studies cited above do not appear to have taken this approach (Lawlor, Windmeijer and Davey Smith, 2008). Rather than basing their selection of genetic variants on associations that are robustly shown in the literature, their choice of instruments seems rather ad hoc: using either forward stepwise estimation (Ding et al, 2009) or selecting those SNPs that have statistically significant sample correlations in the first stage (Fletcher and Lehrer, 2008). In fact, both Ding et al (2009) given that the evidence of a robust association for these variants is lacking, this is not surprising (Lawlor, Windmeijer and Davey Smith, 2008).…”
Section: The Empirical Evidence Using Genetic Variantsmentioning
confidence: 99%
“…Finally, Norton and Han (2008) use several variants as additional controls rather than instruments, as they fail the over-identification tests (SLC6A4, MAOA, DRD2 and CYP2A6). Fletcher and Lehrer (2008) and Ding et al (2009) use several of these as their instruments.…”
Section: The Empirical Evidence Using Genetic Variantsmentioning
confidence: 99%
See 1 more Smart Citation